2022
DOI: 10.3390/md20080529
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Polyketides from the Deep-Sea Cold-Seep Mussel Associated Endozoic Fungus Talaromyces minioluteus CS-138

Abstract: Five new aromatic polyketides, including a unique benzofuran derivative, talarominine A (1), and four chromone analogs talamins A–D (2–5), along with one known related metabolite, 5-hydroxy-7-methoxy-2,3-dimethylchromone (6), were isolated and identified from the Talaromyces minioluteus CS-138, an endozoic fungus obtained from the deep-sea cold seep mussel Gigantidas platifrons. Their chemical structures were elucidated by detailed analysis of their NMR spectra, HRESIMS and X-ray crystallographic data, and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Compound 8 showed weak or no antimicrobial and 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activities [46,58]. In this study, it showed no antiproliferative activity against all tested cancer cell lines (IC 50 > 100 µM) as well.…”
Section: Antiproliferative Activity Of Isolated Compounds Against Thr...mentioning
confidence: 70%
“…Compound 8 showed weak or no antimicrobial and 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activities [46,58]. In this study, it showed no antiproliferative activity against all tested cancer cell lines (IC 50 > 100 µM) as well.…”
Section: Antiproliferative Activity Of Isolated Compounds Against Thr...mentioning
confidence: 70%
“…The antibacterial activities against human pathogenic bacteria ( Escherichia coli and Micrococcus luteus ) and aquatic pathogens ( Vibrio harveyi , Edwardsiella tarda , V. anguillarum , and Aeromonas hydrophilia ) were determined by a serial dilution technique using 96-well microtiter plates with minor modifications, as described in our previous report [ 5 , 6 , 7 , 8 , 9 ]. The bacteria were cultivated overnight at 37 °C in liquid LB medium and diluted with the LB broth to a concentration of 1.5 × 10 8 CFU/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Deep-sea cold seeps are special extreme environments characterized by fluid emissions rich in methane and hydrogen sulfide, developing a unique chemosynthetically-driven ecosystem that creates a unique habitat for microorganisms in sediments [ 4 ]. Recently, a batch of intriguing findings on secondary metabolites from deep-sea cold seep-derived fungi has highlighted the potential of these microbes as a source of new antibiotics [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under extreme conditions, cold seep organisms have evolved unique pathways to produce structurally diverse and biologically active secondary metabolites. According to previous reports, there were a great deal of new compounds that were found in the microorganisms derived from cold seeps, involving alkaloids [ 10 ], polyketides [ 11 ], terpenoids [ 12 ], glycosides [ 13 ], macrolides [ 14 ] and so forth. The new secondary metabolites displayed significant biological activity, including antimicrobial activity, cytotoxic activity and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%